2021
DOI: 10.1021/acs.jpclett.1c00908
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Carbon Deficient Molybdenum Carbide (α-MoC1–x) Enables High-Rate Mg-Ion-based Energy Storage

Abstract: Dual-electron transfer with Mg 2+ -ion intercalation outperforms typical alkali metal-ion (Li + , Na + , K + ) systems with superior charge storage efficiency while the neutral electrolytes can achieve a working voltage beyond the hydrolysis window of 1.23 V. Hence, aqueous Mg-ion electrolytes are promising for electrochemical energy storage devices to boost the energy density and solve the safety challenges synchronously. However, the Mg-based electrochemical energy storage (EES) devices are generally confine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…To verify the reliability of the simulation results, we carried out the CO 2 RR experiment with the MoC 0.66 catalyst. The MoCl 5 hydrogel was carbonized layer by layer through laser ablation to produce the ultrathin MoC 0.66 . , There are some porous structures from ∼10 nm to ∼1 μm distributed in different areas of the MoC 0.66 (Figure S4a). The diffraction pattern results (Figure S4b) indicate that a lattice constant of the MoC 0.66 is 4.25 Å .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify the reliability of the simulation results, we carried out the CO 2 RR experiment with the MoC 0.66 catalyst. The MoCl 5 hydrogel was carbonized layer by layer through laser ablation to produce the ultrathin MoC 0.66 . , There are some porous structures from ∼10 nm to ∼1 μm distributed in different areas of the MoC 0.66 (Figure S4a). The diffraction pattern results (Figure S4b) indicate that a lattice constant of the MoC 0.66 is 4.25 Å .…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction pattern results (Figure S4b) indicate that a lattice constant of the MoC 0.66 is 4.25 Å . Moreover, the high-angle annular dark-field (HAADF) results (Figure S4c) reveal that the carbide sheets are regularly arranged in alternating darker and brighter phases with a crystalline size of approximately 5 nm, and there are plenty of carbon defects in the laser-ablated product, proving the existence of an ultrathin morphology in the experimentally synthesized MoC 0.66 , which is in great agreement with the previous research . An increasing trend of CO 2 conversion (from ∼0.1 to ∼5% under a pressure of 2 MPa for 1 h), representing the better catalytic property of the MoC 0.66 , has been observed by raising the temperature (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that laser irradiation of GO or gelatin-mediated hydrogels/inks containing transition metal ions (Mo 5+ , W 6+ , Co 3+ , V 5+ , etc.) on flexible substrates enable multifunctional TMC-based composites for use in flexible devices including in-plane MSCs. In 2018, Zang et al proposed and demonstrated direct laser writing of Mo 5+ /gelatin-mediated ink-soaked paper substrates using a CW mid-infrared CO 2 laser under an air ambient environment. The resulting product was confirmed to be Mo 3 C 2 and LIG composite characterized by the Raman spectrum and XRD pattern.…”
Section: Laser Processing Techniques For In-plane Mscsmentioning
confidence: 99%
“…[ 17–24 ] This property is known as sub‐stoichiometry, and it plays a vital role in determining bulk properties across many material classes. [ 25–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] This property is known as sub-stoichiometry, and it plays a vital role in determining bulk properties across many material classes. [25][26][27][28] While the presence of vacancies in the dilute limit (≈ 10 −3 ) is usually not sufficient to significantly influence most bulk properties, the concentration of vacancies possible in sub-stoichiometric materials (≈ 10 −1 ) can impart quite considerable effects. For example, vacancy concentration correlates to hardness, [14,29,30] thermal conductivity, [31,32] ionic diffusion, [33,34] and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%